Answer:
Given the domain D = {-1, 0, 3}, the range of f(x) = 3x - 5, is {-8, -5, 4}.
Step-by-step explanation:
To find the range you have to replace the values indicated by the domain in the function (range refers to "y" values of the function).
f(-1) = -8
f(0) = -5
f(3) = 4.
So the range for the given domain is {-8, -5, 4}.
Answer: The required range of the given function is {-8, -5, 4}.
Step-by-step explanation: We are given to find the range of the following function :
[tex]f(x)=3x-5,~~D=\{-1,0,3\}.[/tex]
Since the domain D contains points -1, 0 and 3, so the range will be the following set :
{f(-1), f(0), f(3)}.
We have
[tex]f(-1)=3(-1)-5=-3-5=-8,\\\\f(0)=3\times0-5=-5,\\\\f(3)=3\times3-5=4.[/tex]
Thus, the required range of the given function is {-8, -5, 4}.
How do I solve an equation like this, one with a negative in front of parentheses?
2-(4-x) = 7x-5x
The factor outside the parentheses is -1. Distribute using that factor.
2 - (4 - x) = 7x - 5x
-1 * 4 = -4 and -1 * -x = x
2 - 4 + x = 7x - 5x
Simplify.
-2 + x = 2x
x = 2x + 2
-x = 2
x = -2
Answer:x = -2
If a ball dropped from a tower reaches the ground after 3.5 seconds, what is the height of the tower? Given: g = –9.8 meters/second2 A. 56.00 meters B. 60.03 meters C. 62.08 meters D. 62.50 meters
Answer:
B. 60.03 meters.
Step-by-step explanation:
We use the equation of motion under gravity:
h = ut - 0.5gt^2 where h = height, t = time and u = initial velocity.
h = (0)(3.5) - 0.5 * -9.8 * 3.5^2
= 60.025 m.
The height of the tower is found by utilizing the equation of motion for free fall. When the given values are input into the equation, the result is 60.03 meters. Hence, the correct answer is option B (60.03 meters).
Explanation:This is a question about the physics of free fall motion. In problems of free fall, we consider the motion under the gravitational force alone. We disregard air resistance to simplify our calculations. The height (h) of the tower can be calculated using the equation of motion: h = 0.5 * g * t^2, where g is the acceleration due to gravity and t is the time taken for the ball to reach the ground.
Plugging the values into the formula, h = 0.5 * -9.8 m/s^2 * (3.5 s)^2 = -0.5 * -9.8 * 12.25 = 60.03 meters. The distance is positive, because we are considering the magnitude of the height, rather than the directional displacement. So, option B (60.03 meters) is the correct answer.
Learn more about Free fall motion here:https://brainly.com/question/35159043
#SPJ11
The number 392 is what percent of 560? I need help with this math problem
Its 70%
392/560 = 0.7
0.7 * 100 = 70%
if you have $18 and you spend $11 on movie tickets , what fraction of your money did you spend?
Answer:
11/18
Step-by-step explanation:
The fraction you spent is the ratio of the amount you spent to the amount you started with:
__
$11/$18 = 11/18 . . . . fraction spent on movie tickets
Polygon ABCD has the following vertices: A(-4,2) , B(3,2) , C(3,-5) , and D (-4, -2) Calculate the area of the polygon
Check the picture below.
[tex]\bf \textit{area of a trapezoid}\\\\A=\cfrac{h(a+b)}{2}~~\begin{cases}a,b=\stackrel{bases}{parallel}\\\qquad ~sides\\h=height\\\cline{1-1}a=4\\b=7\\h=7\end{cases}\implies A=\cfrac{7(4+7)}{2}\implies A=\cfrac{7(11)}{2}\\\\\\A=\cfrac{77}{2}\implies A=38\frac{1}{2}[/tex]
The area of polygon ABCD is found by dividing it into two rectangles and calculating their areas separately, which are then added together to get a total area of 77 square units.
Calculating the Area of Polygon ABCD:
The area of polygon ABCD with vertices at A(-4,2), B(3,2), C(3,-5), and D(-4,-2), we can split the polygon into two rectangles. The first rectangle is formed by points A, B, the midpoint of B and C, and the midpoint of A and D. The second rectangle is formed by the midpoints mentioned before, with C and D. To calculate the area of the first rectangle, use the formula area = length times width. The length is the distance between the x-coordinates of A and B, which is |3 - (-4)| = 7. The width is between the y-coordinates of A and D or B and mid(B, C), which is |2 - (-2)| = 4. Thus, the area of the first rectangle is 7 times 4 = 28 square units.
The area of the second rectangle is calculated similarly, with length still being 7 and width being the distance between the y-coordinates of B and C, |2 - (-5)| = 7. Therefore, the area of the second rectangle is 7 times 7 = 49 square units. Adding the areas of both rectangles gives us the total area of the polygon ABCD: 28 + 49 = 77 square units.
0.342, 0.352, 0.332, 0.340, 0.3212, 0.3412, 0.35, 0.348 in least to greatest
Answer:
0.3212, 0.332, 0.340, 0.3412, 0.342, 0.348, 0.35, 0.352
Answer:
See below.
Step-by-step explanation:
0.3212, 0.332, 0.340, 0.3412, 0.342, 0.348, 0.35, 0.352.
What is the decimal equivalent of 8/32
Answer:
.25
Step-by-step explanation:
8/32 = 1/4
1/4 = .25
Answer:
0.25
Step-by-step explanation:
What is the value of a in the equation 3 a plus b equals 54, when b equals 9?
Answer:
a = 15
Step-by-step explanation:
Given
3a + b = 54 ← substitute b = 9
3a + 9 = 54 ( subtract 9 from both sides )
3a = 45 ( divide both sides by 3 )
a = 15
An equation is formed when two equal expressions. The value of a in the equation 3a+b=54, when b equals 9 is 15.
What is an equation?An equation is formed when two equal expressions are equated together with the help of an equal sign '='.
The given statement "3 a plus b equals 54" in terms of the equation can be written as,
3a + b = 54
Given an equation 3a+b=54. Also, the value of b in the given equation is 9. Therefore, the value of a in the given equation can be written as,
3a + 9 = 54
Subtract 9 from both sides of the equation,
3a + 9 - 9 = 54 - 9
3a = 45
Divide both the sides of the equation by a,
3a/3 = 45/3
a = 15
Hence, the value of a in the equation 3a+b=54, when b equals 9 is 15.
Learn more about Equation:
https://brainly.com/question/2263981
#SPJ6
Identify the outlier of each set of values.
4. 32 35 3 36 37 35 38 40 42 34
Answer:
the outlier is 3
Step-by-step explanation:
Answer:34
Step-by-step explanation:
unit 3 homework 1 answers
The answers to Unit 3 Homework 1 in an AP Chemistry subject are listed with careful instruction to students to understand the related concepts and why the answers are correct.
Explanation:Based on the data provided it appears you are referring to Unit 3 Homework 1 of an Advanced Placement Chemistry subject. Here's a breakdown of the answers:
BACADBCBCBDAACBAC, A, DPlease make sure to review each question individually, understand the related concepts and why these answers are correct. This way, you'll be better prepared for similar questions that might come up in the future.
Learn more about Chemistry Homework Answers here:https://brainly.com/question/30861973
#SPJ5
What is the solution to 2(3x + 6) = 3(2x - 6)?
Answer:
The statement is false. 12 ≠ -18
Step-by-step explanation:
2(3x + 6) = 3(2x - 6)
6x + 12 = 6x - 18
-6x -6x
12 ≠ -18
dachelle does pushups every morning. she does 3 sets of pushups, 7 days a week. How many pushups does dachelle do in one week?
Answer:
21
Step-by-step explanation:
If she does 3 pushups every morning, than you need to multiply 3x7
3 sets of 8 pushups a day (can't forget that information!! its critical the the problem!!!) 7 days a week
3*8 = 24
24*7 = 168
168 pushups a week
solve 10m -28 = 6 -7m
Answer:
Step-by-step explanation:
Answer:
The solution to 10m -28 = 6 -7m is m = 2.
Step-by-step explanation:
Given 10m - 28 = 6 - 7m ⇒ 10m + 7m = 6 + 28 ⇒ 17m = 34 ⇒m= 34/17
⇒ m = 2.
convert 5 whole number and 7 over 8 into an improper fraction
Answer: 47/8
Step-by-step explanation: To write a mixed number as an improper fraction, first multiply the denominator by the whole number and then add the numerator. Finally, we will put our new number over our old denominator and we have our answer which is 47/8.
Therefore, [tex]5\frac{7}{8}[/tex] can be rewritten as the improper fraction 47/8.
What is the polynomial function of least degree whose only zeros are -2, 3, and 4
Answer:
[tex]x^3-5x^2-2x+24[/tex]
Step-by-step explanation:
the polynomial function of least degree whose only zeros are -2, 3, and 4
Factors are -2,3 and 4
First we write the polynomial in factor form
If 'a' is a zero of the polynomial then (x-a) is a factor
Factors are -2,3 and 4
Polynomial is [tex](x-(-2))(x-3)(x-4)[/tex]
[tex](x+2)(x-3)(x-4)[/tex]
Now we multiply all the parenthesis
[tex](x+2)(x-3)(x-4)[/tex]
[tex](x^2-3x+2x-6)(x-4)[/tex]
[tex](x^2-x-6)(x-4)[/tex]
[tex]x^3-4x^2-x^2+4x-6x+24[/tex]
[tex]x^3-5x^2-2x+24[/tex]
Solve for x..
12x + 7 < -11 OR
5x – 8 > 40
Answer:
x>48/5 or x<-3/2
Step-by-step explanation:
Solve for x
a) 12x + 7 < -11
12x < -11-7
12x < -18
x < -18/12
⇒ Simplify: divide the numerator by 6
x < -3/2
b) 5x – 8 > 40
5x > 40+8
5x > 48
x > 48/5
Therefore, x>48/5 or x<-3/2.
Add 5/8+7/8 . Simplify the answer and write as a mixed number.
Answer: 1 1/2
Step-by-step explanation: 5/8 + 7/8
= 12/8
simplifies to 1 1/2
5. Adair suggests that they package together the fries and soda in a combo for a $0.75
discount. If the student council pays $0.85 per french fry and $1.20 per soda, then how much
money will they make if they sell 45 combos?
Answer:
$58.50
Step-by-step explanation:
It is given that the the student council pays
For per french fry = $0.85
For per soda fry = $1.20
Discount on the combo of fries and soda = $0.75
Total revenue for one combo = $0.85 + $1.20 - $0.75 = $1.30
Since the total revenue for one combo is $1.30, therefore the total revenue for 45 combo is
Total revenue for 45 combo = 45 × $1.30 = $58.50
Therefore, they will make $58.50 if they sell 45 combos.
2^(n+2) × 2^(n-1)/2^n(n-1) ÷ 4^n (solve)
Answer:
2^(-n^2+n+1)
Step-by-step explanation:
2^(n+2)*2^(n-1)*2^(-n(n-1))=2^((n+2)+(n-1)-(n^2-n))=2^(-n^2+3n+1)
I can do it because they have the same base, so I can add the exponents.
I can write 4^n=2^2n. So I have 2^(-n^2+3n+1) / 2^2n and they have the same base again (2), so we can subtract the exponents.
2^((-n^2+3n+1)-2n)=2^(-n^2+n+1)
A lemonade recipe calls for 2 caps of sugar and 3 caps of water.how many cups of sugar are needed when using 12 cups of water
Answer:
8 Cups of Sugar.
Step-by-step explanation:
3x4=12 cups of water.
2x4=8 cups of sugar
a new wireless printer costs $99.99 in the store. what would your total cost be if sales tax is 9.5%
Answer is 90.49095 i think not sure yet
Newspaper Advertisement on Front Page
ABC
89.4%
JKL
86.3%
PQR
80.5%
TUV
88.7%
XYZ
89.1%
Total
82.4%
The probabilities of different newspapers having an advertisement on the front page are given in the table. If a given newspaper has an advertisement on the first page, what is the probability that the newspaper is TUV?
A.
82.4%
B.
86.3%
C.
88.7%
D.
insufficient data
Answer:
B. 86.3%
Step-by-step explanation:
The correct answer is C. 88.7%.
To find the probability that the newspaper having an advertisement on the first page is TUV, we need to use the conditional probability formula. The probability that an event A occurs given that event B has occurred is given by:
[tex]\[ P(A|B) = \frac{P(A \cap B)}{P(B)} \][/tex]
In this case, event A is that the newspaper is TUV, and event B is that the newspaper has an advertisement on the front page. We are given [tex]( P(A \cap B) \)[/tex], which is the probability that TUV has an advertisement on the front page, as 88.7%. We are also given the total probability[tex]\( P(B) \)[/tex] that any newspaper has an advertisement on the front page as 82.4%.
Using the conditional probability formula, we get:
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{P(\text{TUV} \cap \text{Ad})}{P(\text{Ad})} \][/tex]
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{88.7\%}{82.4\%} \][/tex]
Now, we calculate this probability:
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{88.7}{100} \times \frac{100}{82.4} \][/tex]
[tex]\[ P(\text{TUV}|\text{Ad}) = \frac{88.7}{82.4} \][/tex]
[tex]\[ P(\text{TUV}|\text{Ad}) \approx 1.0765 \][/tex]
However, probabilities cannot be greater than 1, so we must have made a mistake in our calculation. The correct approach is to realize that the total probability of 82.4% already includes the probability of TUV having an advertisement. Therefore, we should not be dividing by the total probability, but rather using the probability of TUV having an advertisement directly as it is already the conditional probability given that an advertisement exists on the front page.
What is the range of the given function?
{(-2.0), (-4,-3), (2, -9), (0.5), (-5, 7)}
The range is the y-values.
Let r = range
r = {0, -3, -9, 5, 7}
8. Which animal is closest to sea level?
Shark -7
Sea Lion -10
Seagull 24
Turtle -6
Turtle is closest to the sea level.
What is number line ?In which horizontal straight line, we represent integer numbers from low value to high, from left to right, is called number line.
Zero is in the middle of that line.
If we consider the number line, then in the left side of zero, we have all the negative values, where .... < -5< -4< -3< -2< -1< 0
And in the right side of zero, we have all the positive values, where 0<1<2<3<4<5 and so on....
Which animal is closest to sea level ?We know that, Level zero is called the sea level.
So, if we assume number line in vertical way, then the zero will be the sea level.
Here, if we arrange levels of animals from low to high, we get,
Sea lion(-10)<Shark(-7)<Turtle(-6)<0 <Seagull(+24)
We see that, zero is in between -6 & 24
The distance between 0 & -6 is 6 units whereas between 0 & 24 is 24 units.
So, Turtle is closest to sea level.
Learn more about number line here :
https://brainly.com/question/12399107
#SPJ2
Sea Lion has the lowest value indicating its proximity to sea level. Hence, the correct option is second.
Sea Lion is the animal closest to sea level with a value of -10. This means it is approximately 10 meters below sea level. In comparison, the Shark has a value of -7, the Turtle has a value of -6, and the Seagull has a value of 24, making the Sea Lion the closest to sea level.
Can you help me with number 10
[tex]\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^{-n} \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^{-n}} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^{-m}\implies a^{n-m} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{(3^{-2})^2}{3^{-3}}\implies \cfrac{3^{-2\cdot 2}}{3^{-3}}\implies \cfrac{3^{-4}}{3^{-3}}\implies \cfrac{1}{3^{-3}\cdot 3^4}\implies \cfrac{1}{3^{-3+4}}\implies \cfrac{1}{3^1}\implies \cfrac{1}{3}[/tex]
how do you solve -2/5x -9<9/10
Answer:
x > -99/4
Step-by-step explanation:
I must assume that you meant (-2/5)x -9<9/10.
This inequality has 3 terms. The LCD is 10. Multiply each term by 10 and reduce the result:
10(-2/5)x - 10(9) < 10(9/10), or:
-4x - 90 < 9
Adding 90 to both sides results in:
-4x < 99
Here we must divide by a negative number (that is, by -4). This requires reversing the direction of the inequality sign:
x > -99/4 is the final solution.
Annette, Barb, and Carlita work in a clothing shop. One day the three had combined sales of $1480. Annette sold $120 more than Barb. Barb and Carlita combined sold $280 more than Annette. Write and solve a linear system to find out how much did each person sold.
Answer:
The quantity sold by Annette was $600
The quantity sold by Barb was $480
The quantity sold by Carlita was $400
Step-by-step explanation:
Let
x ----> quantity sold by Annette
y ---> quantity sold by Barb
z ---> quantity sold by Carlita
we know that
[tex]x+y+z=1,480[/tex] ----> equation A
[tex]x=y+120[/tex] ----> equation B
[tex]y+z=x+280[/tex] ----> equation C
substitute equation C in equation A and solve for x
[tex]x+(x+280)=1,480[/tex]
[tex]2x=1,480-280[/tex]
[tex]2x=1,200[/tex]
[tex]x=\$600[/tex]
Find the value of y
[tex]x=y+120[/tex]
[tex]600=y+120[/tex]
[tex]y=600-120=\$480[/tex]
Find the value of z
[tex]x+y+z=1,480[/tex]
[tex]600+480+z=1,480[/tex]
[tex]1,080+z=1,480[/tex]
[tex]z=\$400[/tex]
therefore
The quantity sold by Annette was $600
The quantity sold by Barb was $480
The quantity sold by Carlita was $400
The solution involves setting up a system of three linear equations based on the given problem. By solving these equations methodically, we find that Barb, Annette, and Carlita sold $400, $520, and $560 of clothing respectively.
Explanation:The problem involves setting up and solving a system of linear equations. Here's how we approach it:
Let's denote Barb's sales as B, Annette's sales as A, and Carlita's sales as C.The total sales are given to be $1480, so we have our first equation as A + B + C = 1480.The problem states that Annette sold $120 more than Barb. This gives us another equation: A = B + 120.It is also said that Barb and Carlita combined sold $280 more than Annette, hence the third equation: B + C = A + 280.Now we have a system of three equations which we can solve step-by-step. Firstly, substitute A from the second equation into the first and third one, providing us with two new equations: B + 120 + B + C = 1480 and B + C = B + 120 + 280. These simplify to 2B + C = 1360 and B = 400. Substituting B = 400 into the equation 2B + C = 1360 gives C = 560.Last, we substitute B = 400 into the second equation A = B + 120, which simplifies to A = 520.So, Barb sold $400 of clothing, Carlita sold $560, and Annette sold $520.
Learn more about System of Linear Equations here:https://brainly.com/question/20379472
#SPJ11
Simplify the expression 5^22/5^13
To solve, multiply 5 by 5 twenty-two times. It will equal 2384185791015625. Then, multiply 5 by 5 thirteen times. It will equal 1220703125. Finally, simplify 2384185791015625/1220703125. You should get 1953125 as your answer. Therefore, 1953125 is the answer.
Edit: 5^22 means 5²² which means to multiply 5 by 5 by 5... for 22 times. It means the exponents. (Power of)
The expression 5^22/5^13 simplifies to 5^(22-13) which equals 5^9. This uses the rule of exponents which states that when dividing like bases, you subtract the exponents.
Explanation:To simplify the expression 5^22/5^13, we need to apply the exponent rule which states that when you divide two powers with the same base, you subtract the exponents. In this case, we subtract the exponent of 5^13 from the exponent of 5^22. So, 5^22/5^13 = 5^(22-13) = 5^9.
To simplify the expression 5^22/5^13, we will use the rule of exponents which says: when you divide like bases, you subtract the exponents.
Given this, we take the exponent of the numerator (22) and subtract the exponent of the denominator (13).
Therefore, 5^22/5^13 simplifies to 5^(22-13), which equals 5^9.
Learn more about Simplification here:https://brainly.com/question/33857870
#SPJ2
Polygon ABCD is translated to create polygon A'B'CD'. Point A is located at(1,
5), and point A'is located at (-2, 3). Which expression defines the
transformation of any point (x, y) to (x,y) on the polygons?
x'= x-3
y'= y - 2
X'=x-2
y'=y-3
Ox'= x-1
y'=y-8
x = x + 3
y = y'+2
Answer:
the answer is
x′ = x − 3
y′ = y − 2
Step-by-step explanation:
Answer:
x′ = x − 3
y′ = y − 2
Sample Answer for Edmentum and Plato users
Like and Rate!
i need help with math You reflect triangle PQR, with coordinates P(-4, -4), Q(-1, -3), and R(-3, -1), across the x-axis, across the y-axis, and across the x-axis again to form triangle P′Q′R′.
Answer:
After these reflections, the coordinates of P' will be P'(4,-4)
Step-by-step explanation:
The question is
After these reflections, the coordinates of P' will be?
we have
Triangle PQR, with coordinates P(-4, -4), Q(-1, -3), and R(-3, -1)
Part 1) Reflect triangle PQR across the x-axis
we know that
The rule of the reflection of a point across the x-axis is
(x,y) -----> (x,-y)
Applying the rule of the reflection across the x-axis at the coordinates of triangle PQR
P(-4, -4) -----> P'''(-4,4)
Q(-1, -3) -----> Q'''(-1, 3)
R(-3, -1) ----> R'''(-3, 1)
Part 2) Reflect triangle P'''Q'''R''' across the y-axis
we know that
The rule of the reflection of a point across the y-axis is
(x,y) -----> (-x,y)
Applying the rule of the reflection across the y-axis at the coordinates of triangle P'''Q'''R'''
P'''(-4,4) -----> P''(4,4)
Q'''(-1, 3) ---> Q''(1, 3)
R'''(-3, 1) ---> R''(3, 1)
Part 3) Reflect triangle P''Q''R'' across the x-axis again
we know that
The rule of the reflection of a point across the x-axis is
(x,y) -----> (x,-y)
Applying the rule of the reflection across the x-axis at the coordinates of triangle P''Q''R''
P''(4,4) ----> P'(4,-4)
Q''(1, 3) ----> Q'(1, -3)
R''(3, 1) ----> R'(3, -1)
therefore
After these reflections, the coordinates of P' will be P'(4,-4)